2020
DOI: 10.1136/tobaccocontrol-2020-056171
|View full text |Cite
|
Sign up to set email alerts
|

Vape shop and consumer activity during COVID-19 non-essential business closures in the USA

Abstract: IntroductionVaping and vape shops pose risk for COVID-19 and its transmission.ObjectivesWe examined vape shop non-compliance with state-ordered business closures during COVID-19, changes in their marketing and experiences among consumers.MethodsAs part of a longitudinal study of vape retail in six metropolitan statistical areas (MSAs; Atlanta, Boston, Minneapolis, Oklahoma City, San Diego and Seattle), we conducted: (1) legal research to determine whether statewide COVID-19 orders required vape shops to close;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…12,15 Prior studies have found that although some e-cigarette users had concerns about product access during the COVID-19 pandemic, many were still able to obtain the products either through stockpiling of products, online purchasing, or from their usual channels either through vape shop non-compliance with or circumventing of business closure orders. [16][17][18] In the present study, factors associated with various forms of stress-total stress, worry about financial problems, and increased working hours-were associated with increased cigarette smoking during the COVID-19 pandemic. A study of current smokers in the United Kingdom during the COVID-19 pandemic also found an association between psychosocial and mental health factors and changes in cigarette consumption.…”
Section: Discussionmentioning
confidence: 52%
“…12,15 Prior studies have found that although some e-cigarette users had concerns about product access during the COVID-19 pandemic, many were still able to obtain the products either through stockpiling of products, online purchasing, or from their usual channels either through vape shop non-compliance with or circumventing of business closure orders. [16][17][18] In the present study, factors associated with various forms of stress-total stress, worry about financial problems, and increased working hours-were associated with increased cigarette smoking during the COVID-19 pandemic. A study of current smokers in the United Kingdom during the COVID-19 pandemic also found an association between psychosocial and mental health factors and changes in cigarette consumption.…”
Section: Discussionmentioning
confidence: 52%
“…In the context of nicotine dependence, rational choice is further impeded by the tobacco-saturated media and retail environments in which people live. Even during the COVID-19 stay-at-home period, many tobacco specialty shops remained open, some in direct opposition of state orders mandating them to close [ 35 ]. Prior criticisms of the HBM have noted the weak effects of tobacco prevention interventions that target rational decision-making processes, as well as the potential for the misuse of such rational choice theories by the tobacco industry in litigation, namely to blame tobacco’s harms on individuals who use it [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that more participants who ever vaped cannabis reported reducing or quitting vaping generally than increasing cannabis vaping is consistent with prior research on the pandemic’s impact on vaping and/or e-cigarette use in this population ( Chaffee et al, 2021 , Dumas et al, 2020 , Gaiha et al, 2020 , Kreslake et al, 2021 , Sokolovsky et al, 2021 , Tattan‐Birch et al, 2021 ). A reduction in cannabis vaping during the pandemic could be due to concerns of susceptibility to COVID-19, disruptions in access to cannabis products, or fewer social engagements with peers ( Berg et al, 202 0 Dumas et al, 2020 , Kreslake et al, 2021 , Tattan‐Birch et al, 2021 ). However, not all young people were deterred from vaping cannabis since most ever-cannabis vapers reported no change and a subgroup reported an increase.…”
Section: Discussionmentioning
confidence: 99%